2021
DOI: 10.1371/journal.pone.0260141
|View full text |Cite
|
Sign up to set email alerts
|

Do exhausted primary school students cheat more? A randomized field experiment

Abstract: Motivated by the two-decade-long scientific debate over the existence of the ego-depletion effect, our paper contributes to exploring the scope conditions of ego-depletion theory. Specifically, in a randomized experiment, we depleted students’ self-control with a cognitively demanding task that required students’ effort. We measured the effect of depleted self-control on a subsequent task that required self-control to not engage in fraudulent cheating behavior—measured with an incentivized dice-roll task—and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Published significant findings numbered around 600 already some years ago (Friese et al, 2019). There are preregistered successful replications (Garrison et al, 2019; Keller & Kiss, 2021) and multiple and diverse non-laboratory real-world findings (e.g., Danziger et al, 2011; Hurley, 2015; Philpot et al, 2018; Trinh et al, 2021). We are hard pressed to find many other findings in social psychology that can match that, except perhaps elaboration likelihood model (see below).…”
Section: Impact On the Fieldmentioning
confidence: 99%
“…Published significant findings numbered around 600 already some years ago (Friese et al, 2019). There are preregistered successful replications (Garrison et al, 2019; Keller & Kiss, 2021) and multiple and diverse non-laboratory real-world findings (e.g., Danziger et al, 2011; Hurley, 2015; Philpot et al, 2018; Trinh et al, 2021). We are hard pressed to find many other findings in social psychology that can match that, except perhaps elaboration likelihood model (see below).…”
Section: Impact On the Fieldmentioning
confidence: 99%
“…Soccer referees perform worse when depleted (Samuel et al, 2018). Students cheat more on tests when depleted (Keller & Kiss, 2021). A large experience sampling study found that people often reported feeling depleted as they went about their daily lives – and reports of depletion were associated with many problems, including more interpersonal conflict and poorer quality of sleep (Baumeister et al, 2019).…”
Section: Generalizability and External Validity Of Self-regulatory De...mentioning
confidence: 99%
“…Acts of selfcontrol cause short-term impairments in subsequent self-control, known as ego depletion [25]. Depleted self-control resources result in impulsive behaviors [26], affecting long-term goals and increasing risk-taking and dishonesty [27,28,29]. Ego depletion also impacts decisionmaking, increasing dishonesty and reducing goal adherence [30,31].…”
Section: Introductionmentioning
confidence: 99%